DETERMINANTS OF INCOME OF FISH PROCESSING MSME ACTORS IN PENGAMBENGAN VILLAGE, JEMBRANA REGENCY - Virgiana Laksita Pramesti; Ni Nyoman Yuliarmi (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The fisheries sector is one of the leading sectors in Bali Province and serves as the backbone of the local economy in Pengambengan Village, Jembrana Regency, Bali. However, it has not yet been optimally developed. This study aims to analyze the simultaneous and partial effects of business capital, education level, technology, raw materials, and working hours on the income of MSME actors in Pengambengan Village, Jembrana Regency. The research employs a quantitative associative approach with a sample of 58 fish-processing MSME actors selected through probability sampling using the simple random sampling method. Data were collected through observation and structured interviews. Data analysis was conducted using descriptive statistics, multiple linear regression, and classical assumption tests. The results of this study indicate that simultaneously, business capital, education level, technology, raw materials, and working hours have a significant effect on the income of fish-processing MSME actors. Partially, the variables of business capital, technology, raw materials, and working hours have a positive and significant effect on income, while the education level variable does not have a significant effect on income. The findings of this study imply the need for outreach regarding capital access and the use of marketing technology to enhance the productivity and welfare of fish-processing MSME actors in a sustainable manner